The effects of junction modifications on sharp-fin-induced glancing shock wave/turbulent boundary layer interaction - Koide, S. (Cranfield University, 1994)
The effects of junction modifications on the glancing shock wave/turbulent boundary layer interaction generated by a sharp fin placed on the wall of a supersonic wind tunnel were examined experimentally at a Mach number of 2.46 and a Reynolds number of 2.59xl06/m. The interactions between a turbulent boundary layer on the wall and shock-wave systems caused by a fin with a fillet and several fins with different strakes were examined individually in order to find an effective modification technique. The flow features obtained by oil flow visualization, surface pressure measurements and liquid crystal thermography were compared with the data from an unmodified fin to evaluate the effects of each modification. The comparisons indicated that a "srake-type" modification had a weakening effect on the interaction-induced separation. To understand the flowfield structures, three-dimensional surveys using laser-light-sheet flow visualization were employed with schlieren photography and oil flow visualization. In addition to these experimental observations, an Euler CFD solver was used to help understand the inviscid flow structures which play important roles in the interaction behaviour. Based on the data experimentally and numerically obtained, a method was proposed for predicting the junction shapes needed to prevent separation.